MODELS OF IMMERSIVE LEARNING ENVIRONMENTS - Rashevska, Natalia (Physical and Mathematical Education, 2026)
The article discusses innovative models developed and implemented to organize learning in an immersive environment. The structure of such models and their advantages in the learning process are highlighted.Formulation of the problem. The development of immersive technologies in education raises the question of designing a comprehensive model of an immersive educational environment that integrates pedagogical, psychological, technological, and developmental factors and meets the conditions of learning in general secondary education institutions. Currently, immersive learning models are fragmented, which complicates their systematic implementation.Materials and methods. The study uses a set of theoretical methods: analysis, systematization, generalization of scientific and pedagogical literature, and structural-functional and comparative analysis of pedagogical models.Results. Five models of immersive learning have been systematized and analyzed: cognitive-affective, research-based, evolutionary, flow state, and game-based learning based on artificial intelligence. Their main characteristics, advantages, and limitations have been identified. It has been established that existing models do not fully account for the specific nature of natural science and mathematics disciplines, as well as the educational needs of high school students. This necessitates further theoretical and practical justification of the integrative approach.  Conclusion. The fragmented nature of the immersive learning models discussed underscores the need to develop a comprehensive model that ensures pedagogical expediency, technological flexibility, and the relevance of learning content in academic lyceums. Further research will focus on creating and testing such a model in the context of studying natural and mathematical disciplines using virtual and augmented reality tools.
Keywords: immersive learning; immersive learning environment; learning organization model; general secondary education institution; academic lyceum; natural science and mathematics subjects